Pengaruh Kualitas Pelayanan Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan (Bagian Service PT. Nasmoco Gombel Semarang) - Naqi Askari; Rodhiyah Rodhiyah; Ngatno Ngatno (Universitas Diponegoro, 2015)
The goal of this study is to determine the effect of service quality on customer loyalty through customer satisfaction variables services servicing. Sampling technique used in this study is purposive sampling technique with samples gathered from 100 people. Linear regression analysis and significance test were used to test the hypotheses using SPSS 22.0. Result of data analysis Quality of service is significantly positive effect on the customer satisfaction (21.7 percent). Quality of service is significantly positive effect on customer loyalty (7.8 percent). Customer satisfaction is significantly positive effect on customer loyalty (16.8 percent). Service quality significantly affect customer loyalty through customer satisfaction (t count > t table). As a suggestion to improvements increase promotion and advertising, organize events aimed at maintaining social relationships with customers, increase awareness and ready to assist customers difficulties.